RESILIENSI EKONOMI MASYARAKAT MELALUI PROGRAM TENAGA KERJA MANDIRI PEMULA (TKMP) DI KECAMATAN CIPOCOK JAYA KOTA SERANG PROVINSI BANTEN - Riny Handayani (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Improving community economic independence through entrepreneurship-based empowerment is one of the goals to be achieved by the Ministry of Manpower of the Republic of Indonesia in collaboration with Sultan Ageng Tirtayasa University (UNTIRTA) through the Beginner Independent Worker Program (TKMP). This program aims to create new entrepreneurs from the unemployed, underemployed, and low-income communities. The long-term goal of this program is to encourage people not only to seek work, but to be able to create their own jobs. The community service activities in this paper aim to analyze the strength or economic resilience of the community through the optimization of the TKMP Program in Serang District, Serang City, Banten. The method used is a participatory approach with the stages of creating a Business Identification Number (NIB), financial management and marketing understanding. The results of the activity show an increase in business legal documents with NIB ownership, increased skills and increased income of participants. Community economic resilience is reflected in the adaptability, resilience, and economic transformation of participants. However, there are several obstacles, especially in the aspect of sustainable assistance, so that strengthened cooperation between the government, academics and the community is needed to support the sustainability of the program. Keywords : Economic Resilience; Community Empowerment; TKMP; Entrepreneurship; Community Service